Dual Functions of MDP Monomer with De- and Remineralizing Ability. (September 2022) - Zheng, H.; Shi, Y.; Bi, L.; Zhang, Z.; Zhou, Z.; Shao, C.; Cui, D.; Cheng, X.; Tang, R.; Pan, H.; Wu, Z.; Fu, B.
Methacryloyloxydecyl dihydrogen phosphate (MDP) has been speculated to induce mineralization, but there has been no convincing evidence of its ability to induce intrafibrillar mineralization. Polymers play a critical role in biomimetic mineralization as stabilizers/inducers of amorphous precursors. Hence, MDP-induced biomimetic mineralization without polymer additives has not been fully verified or elucidated. By combining 3-dimensional stochastic optical reconstruction microscopy, surface zeta potentials, contact angle measurements, inductively coupled plasma–optical emission spectroscopy, transmission electron microscopy, atomic force microscopy, and Fourier transform infrared spectroscopy with circular dichroism, we show that amphiphilic MDP can not only demineralize dentin by releasing protons as an acidic functional monomer but also infiltrate collagen fibrils (including dentin collagen), unwind the triple helical structure by breaking hydrogen bonds, and finally immobilize within collagen. MDP-bound collagen functions as a huge collagenous phosphoprotein (HCPP), in contrast to chemical phosphorylation modifications. HCPP can induce biomimetic mineralization itself without polymer additives by alternatively attracting calcium and phosphate through electrostatic attraction. Therefore, we herein propose the dual functions of amphiphilic MDP monomer with de- and remineralizing ability. MDP in the free state can demineralize dentin substrates by releasing protons, whereas MDP in the collagen-bound state as HCPP can induce intrafibrillar mineralization. The dual functions of MDP monomer with de- and remineralization properties might create a new epoch in adhesive dentistry and preventive dentistry.